Manajemen Pedagogik Guru dalam Mengembangkan Budaya Sekolah Berbasis Tatanen di Bale Atikan Sekolah Dasar - Aris Purwadin; Atik Kurniawati; Iin Sinta; Alwin Mujaiyanah; Nita Nurbaeti; Nisa Lutfi; Nana Herdiana; Revita Yanuarsari (Jurnal Indragiri Penelitian Multidisiplin, 2026)
This study aims to analyze teachers' pedagogical management in developing a school culture based on Tatanén di Balé Atikan (TdBA) in elementary schools in Purwakarta Regency. Using a qualitative approach with a case study method, data were collected through participatory observation, in-depth interviews with nine grade IV–VI teachers and three principals, and document analysis at three public elementary schools in Bungursari District that had implemented TdBA for at least two years. Thematic analysis revealed four dimensions of effective pedagogical management: (1) lesson planning that integrates TdBA values through the Pancaniti framework into subject-specific competencies; (2) implementation of project based learning in school gardens as "living laboratories" emphasizing collaboration (gotong royong) and value modeling through teacher exemplarity; (3) authentic assessment based on process and attitude portfolios aligned with the Sundanese principle of silih asah, coupled with democratic classroom management; and (4) synergy between the principal's visionary leadership and teachers' social competence. Main challenges include tension between the dense national curriculum and flexible time needs, variations in teachers' understanding, limited physical resources, and difficulties in character assessment. The study concludes that holistic pedagogical management by teachers serves as the core driver in transforming TdBA from a ceremonial activity into a living and sustainable school culture.